PENGARUH RESPON UNITED NATIONS ENVIRONMENT PROGRAMME (UNEP) TERHADAP MASALAH TUMPAHAN MINYAK DI DELTA NIGER, NIGERIA TAHUN 2011 - 2017 - Azura "; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The Niger Delta is the largest Delta in Africa and the largest wetland in the world. Located on Niger River, South Nigeria. The people of the Niger Delta are very dependent on the Delta environment. In 1958, for the first time, Shell explored and exploited Niger Delta, which has changed Niger Delta. 1977is the first oil spill revealed in the Niger Delta. The spill problem has not been resolved to this day, and it is also getting bigger every year. The impact of this is not only on the environment around the delta but also very influential on the surrounding community. In 2008, UNEP came and conducted a two-year study in the Niger Delta to meet the demands of the Nigerian government. In 2011, UNEP released on their official website the impact of the oil spill problem in the Niger Delta as well as Delta's cleanup recommendations. The recommendations refer to 3 stakeholders; Government, Oil Company and Delta Niger community. It is hoped that the Recommendations are implemented in a well-implemented and positive impact on the development of the Niger Delta. Key words: United Nations Environment Programme (UNEP), Niger Delta, Oil Spill, Shell